Crab Chitin‐Based 2D Soft Nanomaterials for Fully Biobased Electric Devices. Issue 19 (17th March 2017) - You, Jun; Li, Mingjie; Ding, Beibei; Wu, Xiaochen; Li, Chaoxu
Abstract : 2D nanomaterials have various size/morphology‐dependent properties applicable in electronics, optics, sensing, and actuating. However, intensively studied inorganic 2D nanomaterials are frequently hindered to apply in some particular and industrial fields, owing to harsh synthesis, high‐cost, cytotoxicity, and nondegradability. Endeavor has been made to search for biobased 2D nanomaterials with biocompatibility, sustainability, and biodegradability. A method of hydrophobization‐induced interfacial‐assembly is reported to produce an unprecedented type of nanosheets from marine chitin. During this process, two layers of chitin aggregations assemble into nanosheets with high aspect ratio. With super stability and amphiphilicity, these nanosheets have super ability in creating highly stable Pickering emulsions with internal phase up to 83.4% and droplet size up to 140 μm, in analogue to graphene oxide. Combining emulsifying and carbonization can further convert these 2D precursors to carbon nanosheets with thickness as low as ≈3.8 nm. Having biologic origin, conductivity, and dispersibility in various solvents, resultant carbon nanosheets start a new scenario of exploiting marine resources for fully biobased electric devices with sustainability and biodegradability, e.g., supercapacitor, flexible circuits, and electronic sensors. Hybrid films of chitin and carbon nanosheets also offer low‐cost and environment‐friendly alternative of conductive components desirable in green electronics, wearable electronics, biodegradable circuits, and biologic devices. Abstract : A hydrophobization‐induced interfacial assembly method is developed to produce chitin‐based 2D nanomaterials. Having biologic origin, conductivity, and dispersibility in various solvents, these 2D nanomaterials of chitin and carbon start a new scenario of exploiting marine resources for Pickering emulsion and fully biobased electric devices with sustainability and biodegradability, being applicable in green electronics, wearable electronics, biodegradable circuits, and biologic devices.